Influence of cdp-choline administration on early burn edema in rats - Hernekamp, Jochen-Frederick; Hu, Sissi Xi; Schmidt, Volker-Jürgen; Vogelpohl, Julian; Kneser, Ulrich; Kremer, Thomas (Annals of plastic surgery, 2015)
Purpose - The cholinergic anti-inflammatory pathway may play an important role in early burn edema. Therefore, we evaluated the influence of cdp-choline on early systemic burn edema and leukocyte activation in shock in rat mesenteries after burn plasma transfer. - Methods - Burn plasma harvested from donor rats 4 hours after thermal injury (30% total body surface area, 100°C water, 12 seconds) was administered intravenously to healthy animals during 2 hours of intravital microscopy. Shamburn plasma (same procedure but water at 37°C) was transferred for negative controls. In the study group, bolus injection of 100 mg/kg body weight cdp-choline was undertaken 15 minutes before examination. Intravital microscopy was performed in the ileal portion of rat mesenteries at 0, 60, and 120 minutes. Capillary leakage was assessed by fluorescein isothiocyanate-albumin extravasation and leukocyte-endothelial interaction were observed via transillumination microscopy. To assure comparable hemodynamic conditions, microhemodynamic parameters, foremost venular wall shear rate, were assessed. - Results - Capillary leakage increased significantly after burn plasma transfer when compared to the shamburn group. Additional intravenous administration of cdp-choline attenuates macromolecular efflux to shamburn levels. Leukocyte activation is reduced after cdp-choline treatment. - Conclusions - The significant increase of albumin efflux in rat mesenteries after burn plasma transfer is decreased by additional cdp-choline bolus administration. Further investigations for proof of the relevance of the cholinergic anti-inflammatory pathway in early burn trauma are strongly required.